Glycolysis - a key player in the inflammatory response - Soto Heredero, Gonzalo; Gómez de las Heras, Manuel M.; Gabandé Rodríguez, Enrique; Oller, Jorge; Mittelbrunn, María (My University, 2020)
The inflammatory response involves the activation of several cell types to fight insults caused by a plethora of agents, and to maintain the tissue homoeostasis. On the one hand, cells involved in the pro-inflammatory response, such as inflammatory M1 macrophages, Th1 and Th17 lympho cytes or activated microglia, must rapidly provide energy to fuel inflamma tion, which is essentially accomplished by glycolysis and high lactate production. On the other hand, regulatory T cells or M2 macrophages, which are involved in immune regulation and resolution of inflammation, preferentially use fatty acid oxidation through the TCA cycle as a main source for energy production. Here, we discuss the impact of glycolytic metabolism at the different steps of the inflammatory response. Finally, we review a wide variety of molecular mechanisms which could explain the relationship between glycolytic metabolites and the pro-inflammatory phe notype, including signalling events, epigenetic remodelling, post-transcrip tional regulation and post-translational modifications. Inflammatory processes are a common feature of many age-associated diseases, such as cardiovascular and neurodegenerative disorders. The finding that immuno metabolism could be a master regulator of inflammation broadens the ave nue for treating inflammation-related pathologies through the manipulation of the vascular and immune cell metabolism.